La religión en el emporion - Domínguez Monedero, Adolfo J. (Gerión. Revista de Historia Antigua, 2001)
This paper deals with the religious aspect present in the emporion, seen as one of its main elements. In order to better evaluate the role played by the religious element, a f irst step is to reconsider the evidence of the Homeric Poems as a means to show how religion impregnated all the aspects of the relationships between individuals and societies put into contact. Afterwards, the paper analyses the main evidence for religion in those places visited and frequented by Greeks from the 8th century B. C. onwards. In the last place, a change in Classic times is suggested, when a more economic aspect seems to substitute the religious aspect of the emporion present in the archaic age.